2011
DOI: 10.1177/0269881111421973
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbance in euthymic bipolar patients

Abstract: Objective Sleep disturbance is a common feature during mood episodes in bipolar disorder. The aim of this study was to investigate the prevalence of such symptoms among euthymic bipolar patients, and their association with risk for mood episode recurrence. Method A cohort of bipolar I and II subjects participating in the Systematic Treatment Enhancement Program for Bipolar Disorder who were euthymic for at least eight weeks were included in this analysis. Survival analysis was used to examine the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(90 citation statements)
references
References 34 publications
4
84
1
1
Order By: Relevance
“…Sleep disorders have a high prevalence in euthymic BP. According to the literature, 15-60% of remitted BP show a delayed sleep onset and reduced sleep time, examined by self-report and actigraphy (Brill et al, 2011;Giglio et al, 2009;Sylvia et al, 2012). Moreover, recent research demonstrated that BD is highly associated with sleep and circadian rhythm abnormalities (Murray and Harvey, 2010;Scott, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disorders have a high prevalence in euthymic BP. According to the literature, 15-60% of remitted BP show a delayed sleep onset and reduced sleep time, examined by self-report and actigraphy (Brill et al, 2011;Giglio et al, 2009;Sylvia et al, 2012). Moreover, recent research demonstrated that BD is highly associated with sleep and circadian rhythm abnormalities (Murray and Harvey, 2010;Scott, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…During episodes of depression, insomnia or hypersomnia are common. Even in the inter-episode period, sleep is disturbed; up to 70% of bipolar disorder patients report insomnia 8 , which is associated with risk for relapse and suicide attempts 9 . Hypersomnia is experienced by roughly 25% of bipolar 1 patients during the inter-episode period 10 and by 40–80% during episodes of depression 11 .…”
Section: Why Is Sleep Important In Bipolar Disorder?mentioning
confidence: 99%
“…Prospective relationships between CR disruption and bipolar mood episodes have been reported (Jackson et al, 2003;Murray, 2006;Proudfoot et al, 2011), as well as CR disturbance during euthymia (Gershon et al, 2012;Saunders et al, 2013;Sylvia et al, 2012).…”
Section: Introductionmentioning
confidence: 98%